Problematika Ilmu Falak Kontemporer : Studi Kiblat di Rumah Makan Pinggir Jalan Lintas Kabupaten/Kota se Sumatera Barat - Hendri Hendri; Zul Efendi (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2021)
This study aims to describe the qibla of the prayer room in roadside restaurants across city districts in West Sumatra. This includes how to understand it, the methods used, how accurate the Qibla is. This research found a way to determine the direction of the Qibla, first by estimating, the direction of the sunset, following the surrounding buildings. Second, using a compass, an android Qibla direction software application. So that it affects the accuracy of the Qibla direction based on Rasdhul Qibla. So 15% of the qibla in the roadside prayer room, restaurant is inaccurate or 3 prayer rooms. (from 17 prayer rooms). This is influenced by the lack of understanding, knowledge and information on the Qibla by roadside restaurant owners across districts and cities in West Sumatra